Factors Associated with Food Hygiene Practices Among Street Food Vendors in Padawan, Sarawak - Jores, Drend; Arif, Mohamad Taha; Rahman, Md Mizanur (Borneo Journal of Resource Science and Technology, 2018)
The safety and quality of street foods are still questionable. Street food vendors are often poorly educated and untrained in food safety with lack of food safety knowledge and poor hygiene practice. This study aims to identify the factors associated with hygienic practice of food safety among the streets food vendors in Padawan district, Sarawak. This was a cross-sectional study conducted in Padawan, Sarawak. Data was collected by face to face interview using a validated structured questionnaire. The practice of food safety was observed using a structured observation checklist. Data entry and analysis was done by SPSS version 22.0. A p value <0.05 was considered as statistically significant. A total of 117 street food vendors were interviewed. The mean (SD) age was 41.0 (11.8) years. Three-fifths (62.9%) of the respondents had secondary level of education and higher. The mean (SD) duration of vending was 7.2 (6.7) years. Only 35.9% of the street food vendors received at least one training on food safety. Bivariate analysis revealed that religion, knowledge and attitude appeared to be statistically significant predictors of food safety and hygiene practice. However, multinomial regression analysis revealed that only religion appeared to be important predictor of food safety and hygiene practice (AOR = 14.730, 95% CI: 1.267, 171.228). Although this study failed to establish a statistical significant association between knowledge and attitude with the hygiene practice due to inadequate sample size, some relationship does seem to exist, suggesting that food safety knowledge is vital for all street food vendors to have the necessary skills to enable them to handle food hygienically and ensure food sold is safe for consumption. Keywords: Food safety, food vendors, hygiene practices, Malaysia, Sarawak